Expediting back‐projection algorithm for circular SAR imaging. Issue 10 (1st May 2015) - Li, Haolin; Zhang, Lei; Xing, Mengdao; Bao, Zheng
Abstract : The availability of an expediting back‐projection (EBP) algorithm for circular synthetic aperture radar (CSAR) imaging is investigated. EBP works by dividing the full aperture into sub‐apertures, and using a unified polar grid to generate sub‐images. On the basis of the correspondence between the wavenumber domain and the phase history domain, EBP combines all sub‐aperture spectrums into a full‐aperture one and reconstructs the CSAR image followed by a two‐dimensional (2D) fast Fourier transform. Without time‐consuming 2D interpolation, EBP is capable of decreasing the loss of spectrum, while improving significantly the computational efficiency compared with direct BP.